Diversity, Population Structure, and Above Ground Biomass in Woody Species on Ngomakurira Mountain, Domboshawa, Zimbabwe. (28th July 2016) - Zimudzi, Clemence; Chapano, Christopher
Abstract : The diversity, structure, species composition, and above ground biomass of woody plants on Ngomakurira mountain in Zimbabwe were studied. A systematic random sampling approach was adopted to establish 52 sampling plots measuring 10 × 10 m across 3 study strata in the 1266 ha study area. Woody species occurring in each plot were identified and the circumferences of trees with diameters >8.0 cm at 1.3 m height were measured. A total of 91 species belonging to 74 genera and 39 families were identified in the sample plots. A Shannon-Wiener index mean value of 3.12 was obtained indicating high species diversity on the mountain. The DBH size class distribution showed inverse J distribution patterns across the three study strata, but with only 3 individual plants with DBH > 30 cm. Mean basal area was 15.21 m 2 ha −1 with U. kirkiana and J. globiflora contributing approximately 30% of the basal area. The estimated above ground biomass ranged from 34.5 to 65.1 t ha −1 . Kruskal-Wallis- H test showed no significant differences in species richness, stem density, basal area, above ground biomass, and evenness, across the study strata (p < 0.05 ). Ngomakurira woodland has potential to regenerate due to the presence of many stems in the small diameter size classes.